Next generation sequencing of a custom gene panel to improve the diagnosis of patients with inherited predisposition to colorectal polyposis - Silva, Miguel Ângelo Sota Porto da (2021)
Polyposis syndromes are a group of diseases predisposing to cancer. In general, the genetic mechanisms are well established, but in recente years several pathogenic variants in emergent genes have been associated to theses phenotypes. The main goal of this study was to search for pathogenic variants in emerging genes through a customized next-generation sequencing (NGS) panel in a retrospective series of 189 individuals with a personal/family history of polyposis previously negative for pathogenic variants in the MUTYH and/or APC genes. We also aimed to complete the study of the MUTYH gene in all patients (79 cases) previously studied only for the recurrent/founder +athogenic variants. A total of 18 variants (15 different) were found in 17 patients, seven of them deleterious (six different, two of them in the same patient) and 11 (9 different) variants of uncertain significance (two of them novel). None of the 79 cases previously studied for only the reccurent pathogenic MUTYH variants presented pathogenic variants in the remaining coding regions of this gene. This study demonstrates that pathogenic variants in the emerging genes recently associated in the literature with polyposis are rare.